Congenital Double Lip (A Report of 4 Cases) - Singla, S. P.; Puri, V. K. (Indian Journal of Plastic Surgery, 1986)
Four cases of congenital double lip are reported along with discussion on aetiological and epidemiological aspects of this anomaly.